The "chimney forest" of the deep Montenegrin margin, south-eastern Adriatic Sea. (September 2015) - Angeletti, L.; Canese, S.; Franchi, F.; Montagna, P.; Reitner, J.; Walliser, E.O.; Taviani, M.
Abstract: A spectacular field of columnar carbonates has been discovered on the Montenegrin margin in the southern Adriatic Sea at a depth of about 450 m. The site exposes many columnar carbonates protruding from the substrate or abated on the bottom. Such carbonates attain maximum visible lengths of ca. 60 cm with diameters up to 20 cm; display an annular growth, and are either hollow or plugged by indurated sediment. Petrographic and geochemical analyses document the pervasive presence of dolomite, and δ 13 C values as low as −30‰ VPDB. These 'chimneys' are therefore interpreted as former conduits related to hydrocarbon expulsion in this sector of the Adriatic basin. However, available data suggest that hydrocarbon flows at this site have ceased. Our results show that chimneys formed inside the local depositional units, glacial Pleistocene shelf shelly-rich muddy sediment and were successively exhumed from the host sediment. Today, the chimneys offer substrate to benthic life, including cold water corals and sponges. The U-series dating of these carbonate concretions is complicated by the presence of a significant fraction of detrital sediment, which represents a major source of initial 230 Th. AMS- 14 C and 87 Sr/ 86 Sr dating of shells embedded in one of the chimney provided ages beyond the range of radiocarbon dating and <600 kyrs, indicating a Pleistocene age of the host sediment. Uncorrected U-series dating of the carbonate chimneys yielded and age of ca. 250–270 kyrs, providing a temporal upper limit for conduit formation driven by lithification caused by the degradation of seeping hydrocarbons. In addition, U/Th dating of cold water coral bases settled on chimneys indicates a Holocene age for their first exposure after exhumation and subsequent function as hard substrate for benthic organisms. The Montenegrin 'chimney forest' is a rare case where many such carbonate columnar concretions are still in their original vertical position. Highlights: First record of a submerged seep-carbonate conduit field in the Mediterranean. Chimneys are dolomitic and share analogies with outcrop counterparts. Mark hydrocarbon seepage in the Pleistocene of the S Adriatic Sea.